Klebsiella spp. carried by insects as a reservoir of virulence and resistance to antimicrobials - Isabel Carramaschi; Leticia Miranda Santos Lery; Thiago Pavoni Gomes Chagas; Viviane Zahner (One Health)
Synanthropic flies contribute to the transport of pathogens between environments, but their role remains underexplored. Previously, our group described 197 bacterial strains obtained from 117 dipterous muscoids collected nearby hospitals in Rio de Janeiro, 35 % showing antimicrobial resistance. Ten isolates belonged to Klebsiella genus. Klebsiella pneumoniae is a threat to human health due to high resistance and virulence. We characterized the 10 isolates from the genus Klebsiella isolated from flies, comparing to 4 from patients. Most carried resistance determinants as blaSHV and blaNDM. One of them was MDR. Isolates from flies included ST219 and ST76, clinically relevant. Efflux pumps and porins were sporadically encoded in both fly and clinical samples. Among 10 virulence determinants, fly-isolated strains presented from 2 to 7 genes, while clinical strains ranged from 4 to 6. Notably, fly-isolated formed higher biofilm than clinical. Our findings underline that environmental resistance reservoirs may undermine efforts to control AMR.